Non - prescription drugs - Po, Alain Li Wan (Oxford, United Kingdom : Blackwell Publishers, 1990)
A comprehensive reference which covers currently available non-prescription drugs, their indications, adverse effects, dosage and formulation. This second edition has been completely revised.
Part I: Introduction -- Part II: The skin -- Part III: The oral cavity and the gastrointestinal tract -- Part IV: The upper respiratory tract -- Part V: The urinary tract -- Part VI: The reproductive system -- Part VII: Analgesia -- Part VIII: The eye -- Part IX: The ear -- Part X: Malaria -- Part XI: Sleep aids.
Includes bibliographical references and index.
Keywords: DRUGS, NONPRESCRIPTION